The Effectiveness of Humic Acid and Trichoderma sp. for Planting Media with Oil Palm Empty Bunches in Pakcoy (Brassica rapa L.) - Aline Sisi Handini; Ratih Rahhutami; Dwi Astutik (International Journal of Multi Discipline Science, 2020)
Pakcoy is a vegetable commodity that has high economic value. This study aims to determine the effect of humic acid and Trichoderma sp. by utilizing empty fruit bunch (EFB) waste as a growing medium for Pakcoy growth. The research method used was a two-factor randomized block design. The first factor is humic acid (AH) with three levels: AH1 = 1 g, AH2 = 2 g, AH3 = 3 g. The second factor is Trichoderma sp. (T) with three levels; T1 = 50 ml, T2 = 100 ml, T3 = 150 ml. In this study it was concluded, the best treatment was found in the application of humic acid with a dose of 1 g on the parameters of observation of leaf length, leaf width, plant height, wet weight, and plant dry weight. The use of Trichoderma sp. in this study, does not affect all parameters observation. The results of the analysis of the planting medium showed that the pH was slightly acidic conditions 5.67 - 6.33. The organic matter content contained in the growing media ranged from 1.20 to 2.62%, and the total N-total contained in the growing medium ranged from 0.10 to 0.18. In-plant tissue analysis shows that the N-total found in plant tissue ranges from 4.62 - 5.23.